Analisis Strategi Pemasaran Dalam Meningkatkan Jumlah Nasabah Pada Perusahaan Pembiayaan Berbasis Teknologi Finansial (Studi Kasus Pt. Nsc Finance Mamuju) - Hatta, Fiqra Ramadhan; Salmiah; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
This research aims to analyze marketing strategies in increasing the number of customers at a financial technology (fintech)-based financing company, with a case study at PT. NSC Finance Mamuju. The research method used is a descriptive quantitative approach, with data collection techniques through questionnaires distributed to customers and prospective customers of PT. NSC Finance Mamuju, supported by literature studies and documentation. Data analysis is carried out using validity tests, reliability tests, and descriptive analysis to assess the influence of marketing strategies, which include the marketing mix (7P), segmentation, targeting, positioning, and digital marketing, on the increase in the number of customers. The results of the study indicate that marketing strategies have a significant effect on increasing the number of customers, especially in aspects of digital promotion, service quality, and the ease of the financing process. This research is expected to serve as an academic and practical reference for fintech financing companies in formulating effective and sustainable marketing strategies.